2014
DOI: 10.1128/iai.01393-13
|View full text |Cite
|
Sign up to set email alerts
|

Role of Urinary Cathelicidin LL-37 and Human β-Defensin 1 in Uncomplicated Escherichia coli Urinary Tract Infections

Abstract: ; Haslev Laegecenter, Haslev, Denmark c ; Laegehuset Ellemarksvej, Køge, Denmark d Cathelicidin (LL-37) and human ␤-defensin 1 (hBD-1) are important components of the innate defense in the urinary tract. The aim of this study was to characterize whether these peptides are important for developing uncomplicated Escherichia coli urinary tract infections (UTIs). This was investigated by comparing urinary peptide levels of UTI patients during and after infection to those of controls, as well as characterizing the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(65 citation statements)
references
References 34 publications
3
60
1
1
Order By: Relevance
“…The human intestine is a major reservoir for extra-intestinal pathogenic E. coli strains; especially, urinary tract infections are mostly caused by patients' own faecal E. coli (Ejrnaes, 2011;Nielsen et al, 2014). Faecal E. coli is also a frequent cause of extra-intestinal infections in infants in the form of meningitis and blood sepsis (Korhonen et al, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…The human intestine is a major reservoir for extra-intestinal pathogenic E. coli strains; especially, urinary tract infections are mostly caused by patients' own faecal E. coli (Ejrnaes, 2011;Nielsen et al, 2014). Faecal E. coli is also a frequent cause of extra-intestinal infections in infants in the form of meningitis and blood sepsis (Korhonen et al, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…53,80 Mature HBD-1 is constitutively detected in sterile urine at concentrations of 10-100 μg/l or 3.5-316 mg/g of creatinine, with higher urinary levels in pregnant women. 53,62 Urinary HBD-1 levels increase up to threefold in patients with acute pyelonephritis, whereas by contrast, studies suggest HBD-1 levels are not induced in cystitis. 62,81 In women undergoing pelvic floor surgery for urinary incontinence or pelvic organ prolapse, urinary HBD-1 levels were lower in patients with preoperative positive urine cultures.…”
Section: β-Defensinsmentioning
confidence: 93%
“…Low levels of LL-37 are detected in sterile urine and urinary LL-37 concentrations increase in the presence of cystitis and pyelonephritis. 61,62 In human kidney biopsy specimens, LL-37 production increased following exposure to UPEC. 61 Similarly, administration of UPEC to renal epithelial cells (A498 and hPTC cells) and urothelial cells (J82 and UROtsa cells) in vitro resulted in rapid increases in CAMP mRNA expression followed by prolonged LL-37 peptide secretion.…”
Section: Cathelicidin Antimicrobial Peptidementioning
confidence: 98%
“…For instance, the protein beta defensin-1 (BD1) and Cathelicidin (LL-37) peptide shows constitutive expression in the urinary tract, as both molecules from previous studies have demonstrated to play key roles in UTI's mitigation (Mambula et al, 2000;Chromek et al, 2006). Also, in a study of uncomplicated UTI subject, elevated level of LL-37 was observed (Nielsen et al, 2014), whilst E. coli isolates from healthy controls exhibited more susceptibility to LL-37 than isolates from UTI patients. Further, BD1 has also exhibited constitutive expression in the urinary tract and hence, BD1 is suggested to play a role in pyelonephritis (Smith et al, 2011;Mambula et al, 2000;Morrison et al, 2002) and act as a defence against Gram-positive uropathogens (Morrison et al, 2002).…”
Section: Discussionmentioning
confidence: 95%